Multilevel and Biometric-Graphical Secure Authentication System Using Pattern Matching and Gene Based Data Extraction (International Journal of Engineering and Computer Science, 2018)
In computer science considering the large scale network and increasing number of application, the protection and security of the system is essential. The Information Technology System is improving day by day. The growing concern of computer science technology creates problem for identity theft problems, hence protection and computer system security is playing vital role. The conventional alphanumeric password protection system is very vulnerable. This kind of alphanumeric password can be traced and difficult to remember for the system user. This leads to a new era of protection and security system in case of authenticity in computer science. In this paper, it is proposed to have very user-friendly secure multilevel biometric graphical authentication system. This kind of authentication system is easy for authorized user but very difficult to un-authorized user to trace. The multilevel and biometric-graphical secure authentication system algorithm described here uses more than one level of authentication system such as face detection, DNA finger printing, image pattern matching and alphanumeric password with image pattern. This algorithm based on entities that are actually bound with the individual at a much secure level than. As a result, they are more reliable since biometric information cannot be lost, forgotten, or guessed easily.